"Wild cannabis": A review of the traditional use and phytochemistry of Leonotis leonurus. (4th November 2015) - Nsuala, Baudry N.; Enslin, Gill; Viljoen, Alvaro
Abstract: Ethnopharmacological relevance: Leonotis leonurus, locally commonly known as "wilde dagga" (=wild cannabis), is traditionally used as a decoction, both topically and orally, in the treatment of a wide variety of conditions such as haemorrhoids, eczema, skin rashes, boils, itching, muscular cramps, headache, epilepsy, chest infections, constipation, spider and snake bites. The dried leaves and flowers are also smoked to relieve epilepsy. The leaves and flowers are reported to produce a mild euphoric effect when smoked and have been said to have a similar, although less potent, psychoactive effect to cannabis. Aim of the review: To amalgamate the botanical aspects, ethnopharmacology, phytochemistry, biological activity, toxicity and commercial aspects of the scientific literature available on L. leonurus . Methods: An extensive review of the literature from 1900 to 2015 was carried out. Electronic databases including Scopus ®, SciFinder®, Pubmed ®, Google Scholar ®  and Google ®  were used as data sources. All abstracts, full-text articles and books written in English were considered. Results: The phytochemistry of particularly the non-volatile constituents of L. leonurus has been comprehensively investigated due to interest generated as a result of the wide variety of biological effects reported for this plant. More than 50 compounds have been isolated and characterised. L. leonurus contains mainly terpenoids, particularly labdane diterpenes, the major diterpene reported is marrubiin. Various other compounds have been reported by some authors to have been isolated from the plant, including, in the popular literature only, the mildly psychoactive alkaloid, leonurine. Leonurine has however, never been reported by any scientific analysis of the extracts of L. leonurus. Conclusion: Despite the publication of various papers on L. leonurus, there is still, however, the need for definitive research and clarification of other compounds, including alkaloids and essential oils from L. leonurus, as well as from other plant parts, such as the roots which are extensively used in traditional medicine. The traditional use by smoking also requires further investigation as to how the chemistry and activity are affected by this form of administration. Research has proven the psychoactive effects of the crude extract of L. leonurus, but confirmation of the presence of psychoactive compounds, as well as isolation and characterization, is still required. Deliberate adulteration of L. leonurus with synthetic cannabinoids has been reported recently, in an attempt to facilitate the marketing of these illegal substances, highlighting the necessity for refinement of appropriate quality control processes to ensure safety and quality. Much work is therefore still required on the aspect of quality control to ensure safety, quality and efficacy of the product supplied to patients, as this plant is widely used in South Africa as a traditional medicine. Commercially available plant sources provide a viable option for phytochemical research, particularly with regard to the appropriate validation of the plant material (taxonomy) in order to identify and delimit closely related species such as L. leonurus and L. nepetifolia which are very similar in habit. Graphical abstract: